2016
DOI: 10.1093/ehjci/jew292
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic cardiomyopathy with aortic dilation: a novel observation

Abstract: We report a novel observation with 9.0% prevalance of dilated aorta in HCM patients. Further studies are needed to help define the genetic and pathophysiologic basis as well as the clinical implications of this association in a larger group of HCM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Our data show that the absence of Metrnβ causes development of an abnormal pattern of asymmetric hypertrophy, with the most severe hypertrophy involving the basal IVS, interstitial fibrosis, aortic dilation, and left ventricular dysfunction. This phenotype, which shows a pattern more characteristic of cardiac dysfunction than of non-asymmetrical hypertrophy, resembles that in patients with hypertrophic cardiomyopathy ( Marian and Braunwald, 2017 ; Yousefzai et al, 2017 ), one of the leading causes of sudden death among young people ( Maron and Maron, 2013 ). Although it has been shown that hypertrophic cardiomyopathy may be inherited ( Katayama et al, 2018 ), it seems unlikely that the effects observed in our global KO model are early development related, since basal signs of cardiac hypertrophy do not develop spontaneously in young Metrnβ-null mice.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our data show that the absence of Metrnβ causes development of an abnormal pattern of asymmetric hypertrophy, with the most severe hypertrophy involving the basal IVS, interstitial fibrosis, aortic dilation, and left ventricular dysfunction. This phenotype, which shows a pattern more characteristic of cardiac dysfunction than of non-asymmetrical hypertrophy, resembles that in patients with hypertrophic cardiomyopathy ( Marian and Braunwald, 2017 ; Yousefzai et al, 2017 ), one of the leading causes of sudden death among young people ( Maron and Maron, 2013 ). Although it has been shown that hypertrophic cardiomyopathy may be inherited ( Katayama et al, 2018 ), it seems unlikely that the effects observed in our global KO model are early development related, since basal signs of cardiac hypertrophy do not develop spontaneously in young Metrnβ-null mice.…”
Section: Discussionmentioning
confidence: 62%
“…The parameters of diastolic function E peak and mitral deceleration were altered in Metrnβ −/− mice: E peak tended to increase in Metrnβ −/− mice after ISO treatment (P = 0.06), and mitral deceleration was significantly reduced in mice lacking Metrnβ, indicating reduced relaxation times during diastole. Collectively, these data indicate that the asymmetrical hypertrophy developed in Metrnβ −/− mice is associated with a higher degree of contractility necessary to compensate the thickening of the septal wall, a phenotype resembling patients with hypertrophic cardiomyopathy ( Marian and Braunwald, 2017 ; Yousefzai et al, 2017 ).…”
Section: Resultsmentioning
confidence: 85%
“…While aortic stiffness has been proven to be increased in patients with OHCM, 3 recent data have suggested an increased prevalence of aortic dilatation, although there is no clear consensus. 2 To our knowledge, this is the first case report describing a combined surgical intervention on OHCM and aortic aneurysm. Ours is a reference center for OHCM, with 570 cases surgically treated between 2013 and 2019.…”
Section: Discussionmentioning
confidence: 80%
“…A recent study described an increased prevalence of dilated aorta (DA) in HCM [2] , but another study failed to demonstrate the association [3] . Both of these studies were limited by small sample size as well as weak epidemiological study designs, i.e., both were case series ( Table 1 ) [2] , [3] , [4] , [5] , [6] . Neither of them had a well-constructed case-control design.…”
Section: Introductionmentioning
confidence: 99%